Land use effects on labile N extracted with permanganate and the nitrogen management index in the Cerrado region of Brazil - Westerhof, R; Vilela, Lourival; Ayarza, Miguel Angel; Zech, W. (Springer, 1998)
The effect of land use on the availability of nitrogen (N) was studied by separating total N into a labile and a stable fraction by oxidation and extraction of labile N with KMnO4. The nitrogen management index (NMI) was calculated following the method of Blair et al. (1995) for the carbon management index. In all systems, labile N released by KMnO4 was a better indicator of N availability than total and stable N. The NMI was a good indicator of N availability but gave no information about the total amount of N. In land use system analysis, total N and labile N can be used together as a simple and rapid way to evaluate the N status of the soil. Legume-based pastures specifically increased the amount of labile N. Although soybeans had a dominant role in the continuous cropping systems studied, the total N contents of these systems were lower than those of the natural Cerrado. The availability of N under legume-based pastures and legume-based pasture-crop rotations was higher than under the natural Cerrado and the continuous cropping systems.